Yield and nutritive quality of five sweet potato varieties in response to four levels of nitrogen fertilizer - Vosawai, Ratu Penaia (2013)
Sweet potato (Ipomoea batatas (L.) Lam) is an important food in developing countries that is rich in beta-carotene and vitamins. A field experiment was conducted in UPM to evaluate the response of yield and yield components and nutritive quality of five sweet potato varieties planted on two different sites with four levels of nitrogen fertilizer applied. The experiment used a split plot design with nitrogen as main plot in three replications and variety as the subplots. The nitrogen fertilizer levels used were 0, 17, 34 and 68 kg N/ha and the varieties were from UPM germplasm collection of sweet potato obtained from various parts of Malaysia. The varieties were labelled A, B, C, D and E. The results showed that nitrogen fertilizer rates affected yield components, including fresh tuber yield, vine length, and leaf number and stomatal conductance. The response curves obtained indicated an optimum fertilizer rate of 50 kg N/ha is recommended in Field 2 and 40 kg N/ha in Field 10. The highest fresh tuber yield was 14 t/ha in Field 2 and 3 t/ha in Field 10. The differences were attributed to better soil texture and fertility in Field 2 compared to Field 10. Application of nitrogen fertilizer to sweet potato also affects its nutritive quality. Application of 50 kg N/ha in Field 2 and 40 kg N/ha in Field 10 favors the nutritive quality in sweet potato tuber in terms of total sugar, beta-carotene, vitamin C, protein and fat.